EVALUASI KEBIJAKAN KOTA LAYAK ANAK PEMENUHAN KLASTER V PERLINDUNGAN KHUSUS DI KOTA SEMARANG - Anjela Laurensia Turnip; Augustin Rina Herawati (Journal of Management and Public Policy, 2026)
The high number of child violence cases in the City of Semarang forms the background of this research, despite the existence and implementation of the Child Friendly City (Kota Layak Anak/KLA) policy, particularly within the Special Protection Cluster, which has not yet been optimally fulfilled. This study aims to evaluate the implementation of the Child Friendly City (KLA) policy in Semarang, specifically in meeting the requirements of the Special Protection Cluster. This research employs a qualitative approach using the CIPP (Context, Input, Process, Product) evaluation model to obtain a comprehensive overview of the policy context, available resources, implementation processes, and achieved outcomes. Data collection techniques include in depth interviews, observation, and document analysis involving relevant government agencies and target groups. The findings indicate that in the implementation of the Child Friendly City policy, particularly in fulfilling Cluster V Special Protection, several obstacles remain, resulting in suboptimal implementation. The achievement of the “Main” category Child-Friendly City award does not necessarily indicate that children in Semarang are fully protected. The fact that not all areas of Semarang have been reached demonstrates that child protection efforts are not yet evenly distributed. This condition is influenced by various inhibiting factors, such as the limited number of human resources, the absence of clear success indicators, and a lack of commitment among policymakers. Overall, the implementation of the Child Friendly City policy in fulfilling Cluster V Special Protection has been carried out but has not yet been fully optimal in both preventive and curative aspects. Therefore, improvements are still needed in several areas, including strengthening coordination among the Gugus Tugas KLA, establishing an integrated reporting system, and reinforcing the commitment of the Task Force to ensure that children can grow and develop in a safe environment.